The effect of Atherogenicity index in Type 2 Diabetes mellitus patients and it is association with chronic cardiovascular complications of the disease - Alyaa Hasan Bohan (Al-SalamJournal for Medical Science)
Atherosclerotic cardiac disease (ASCVD) is a significant health issues among people who have Type 2 diabetes mellitus (T2DM). Diabetic patients experience ASCVD-related consequences 14.6 years faster than non-diabetic individuals. The main goal of the study was to assess the relevance of the atherogenic index of plasma (AIP) and other lipid-related indicators in predicting ASCVD risk in Iraqi T2DM patients.